The Grammar of Indifference: Tocqueville and the Language of Democracy. (August 2017) - Avramenko, Richard
This essay analyzes what Alexis de Tocqueville calls an "application of linguistics to history." Beginning with Tocqueville's position that language is the ground of meaningful bonds between people, I argue that the internal logic of a language—the grammar—is correlated with the internal logic governing the social order that both begets and is begotten by that language. Social orders therefore have both linguistic and political grammars and, as the internal logic of language changes, so too can the political grammar. This essay thus traces what Tocqueville envisions as the historical importance of language: from the language of aristocracy and the grammar of difference, to revolutionary language and the grammar of concurrence, to democratic language and the grammar of indifference. It concludes with Tocqueville's suggestion of how good grammar might be taught in democratic ages.